The effect of a new coronavirus infection caused by the SARS-CoV-2 virus on microcirculation in the conjunctiva - T. N. Safonova; G. V. Zaitseva; N. P. Kintyukhina (Медицинский совет, 2022)
Introduction. The availability of an objective assessment of the microcirculatory bed is possible when examining the vessels of the conjunctiva. This is especially true in individuals who have had COVID-19 and have diseases associated with endothelial dysfunction.Aim. To study the microcirculation in the conjunctiva after a new coronavirus infection caused by the SARS-CoV-2 virus.Materials and methods. 83 patients with a history of coronavirus infection were examined. Patients were divided into 2 groups depending on the presence or absence of comorbidities. Group 1 patients (n = 42) with post-COVID changes in the conjunctiva (severe  injection of  the eyeball, chemosis, microhemorrhagia, folliculosis of  the tarsal and bulbar conjunctiva, the  presence of  a  nodular formation  (conflicts), slight edema of  the corneal epithelium) and a  history of  concomitant diseases: arterial hypertension, diabetes, coronary heart disease, atherosclerosis. Group 2 patients (n = 41) with no history of concomitant diseases and similar post-COVID changes in  the conjunctiva. The control group consisted of  healthy volunteers without a  history of coronavirus infection (n = 30). All subjects underwent laser Doppler flowmetry of the bulbar conjunctiva 3, 6, 12 months after the coronavirus infection.Results and discussion. In comparison with the control group of persons after 3 months, microcirculatory disorders were detected in both groups (group 1 – subcompensated, group 2 – decompensated). In group 1, after 6 months and 12 months, violations persisted in  the subcompensation stage, which were accompanied by an increase in  the intensity of  the functioning of  the regulatory systems of the microcirculation: the M index corresponded to normal values, and the values of σ and Kv were above the norm. After 6 months in group 2, compensation of microcirculatory disorders was noted (indicators M, σ, Kv were normal), which persisted even by 12 months of observation.Conclusion. The data obtained indicate that in patients with concomitant endothelial dysfunction, the processes of restoration of the microvasculature are slowed down.